Upaya dalam Menangani Problem Etika dalam Fisafat Ilmu - Mardinal Tarigan; Sania Oktavia Nasution; Siti Sholikhah; Najwa Al Zuhda Sitorus; Dwi Fathimah (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Philosophy of science is a true knowledge that occurs in a judicial manner regarding an object of knowledge obtained from a point of view or method used. According to one expert says that " The philosophy of science is a part of philosophy that tries to do for science what philosophy generally does to the whole human experience." ( Peter Caws ). In essence, every human being who has knowledge must have ethics in solving some of life's problems. Therefore, in addition to academic knowledge that is continuously mastered, ethical science also needs to be balanced in the process of self-maturation so that later oneself will have good character and ethics to become a leader.